2022
DOI: 10.3390/rs14061310
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Ecosystem Functioning in Spain with Gross and Net Primary Production Time Series

Abstract: The main objective of this study is to analyze the spatial and temporal variability of gross and net primary production (GPP and NPP) in Peninsular Spain across 15 years (2004–2018) and determine the relationship of those carbon fluxes with precipitation and air temperature. A time series study of daily GPP, NPP, mean air temperature, and monthly standardized precipitation index (SPI) at 1 km spatial resolution is conducted to analyze the ecosystem status and adaptation to changing environmental conditions. Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Through comparative analysis, we found that our MRCNN downscaling algorithm produced results that aligned significantly more with the MODIS NDVI for the selected five features. This finding suggests that our algorithm can more accurately represent the true characteristics of these features, providing substantial practical significance [92][93][94]. When we conducted individual examinations of each year for the five features as discrete intervals, our method demonstrated marginally superior correspondence with MODIS NDVI compared to the other four methods, despite overall improvements.…”
Section: B Comparison With Previous Studiesmentioning
confidence: 90%
“…Through comparative analysis, we found that our MRCNN downscaling algorithm produced results that aligned significantly more with the MODIS NDVI for the selected five features. This finding suggests that our algorithm can more accurately represent the true characteristics of these features, providing substantial practical significance [92][93][94]. When we conducted individual examinations of each year for the five features as discrete intervals, our method demonstrated marginally superior correspondence with MODIS NDVI compared to the other four methods, despite overall improvements.…”
Section: B Comparison With Previous Studiesmentioning
confidence: 90%
“…Concurrently, escalating human activities, such as uncontrolled resource extraction, human-induced forest fires, the invasion of alien species, and forest clearance due to population expansion, exert considerable adverse effects on forest ecosystems [13,14]. Research on the global carbon cycle, especially in the context of climate change and human activities, has become a core issue in the field of environmental science [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al referred to the drought-stress improved-EC-LUE model to estimate the spatiotemporal distribution pattern of GPP in the Mao bamboo forest of Anji City [28]. Martínez et al applied the GLO-PEM model to estimate the net primary productivity of the Iberian Peninsula for 15 years and studied its spatial and temporal variations and the quantitative relationship between NPP, precipitation, and air temperature [21]. Although many scientific studies have used light use efficiency models to study vegetation productivity, currently most LUE models directly simulate the GPP, with only the CASA and GLO-PEM models capable of directly simulating the NPP [23].…”
Section: Introductionmentioning
confidence: 99%
“…From the research content, there were long-term NDVI temporal and spatial evolution and future sustainability analysis [20,21], the detection of driving factors [20], and the correlation analysis of NDVI, terrain, climate, and other elements [17,22], as well as mutation analysis of vegetation NDVI [23]. The commonly used research methods mainly include the linear regression analysis method [24,25], correlation analysis method [17,21,26], trend analysis method combining Theil-Sen slope and Mann-Kendall test [7,27,28], and Hurst exponent method [21,29]. Typical studies using these methods are as follows: Zhang et al detected the long-term trends and abrupt changes of urbanized area by the Theil-Sen estimator and Mann-Kendall test [30], Yan et al employed the Mann-Kendall test to test the significance of LAI [31], Tehrani et al used the Mann-Kendall test to perform a correlation analysis of two months during the epidemic of COVID-19 [32], etc.…”
Section: Introductionmentioning
confidence: 99%